Code-Switching And Personality Shift: Analyzing Introversion And Extroversion In Bilinguals (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Through extensive literature analysis and analysis, this article explores how the study exhibits different personality traits depending on the language used by bilingual individuals. The study studies the psychological and sociolinguistic factors that contribute to these changes, as well as their impact on personal and professional relationships. The results suggest that languagerelated personality changes are common among bilinguals, potentially affecting social behavior, emotional expression, and cognitive processes.